Relationship between energy consumption and macroeconomics variables : Case of Malaysia / Aliff Haiqal Mohd Fadzli - Mohd Fadzli, Aliff Haiqal (2018)
This study is conducted in order to investigate the relationship between energy consumption, economic growth, consumer price index and labour force in Malaysia. Econometrics analysis is used in this study to achieve the goal of this study taking the period of 1991-2015. The finding validates that economic growth and labour force has positive and statistically significant impact on energy consumption while consumer price index has negative relationship with energy consumption. The result of this study motivated researcher to recommend that this country need to being efficient in their using of energy especially in industrial area, the waste of energy may lead to the higher price which the burden will bear by the population of the country and in order to reduce the unnecessary waste of energy they need to increase in energy conservation.